Multidrug-Resistant Enterococcus faecium and Enterococcus faecalis Isolated from Dogs and Cats in Southern Brazil - Letícia da Silva; Cristina Zaffari Grecellé; Ana Paula Guedes Frazzon; André Felipe Streck; Diéssy Kipper; André Salvador Kazantzi Fonseca; Nilo Ikuta; Vagner Ricardo Lunge (Microbiology Research)
Enterococcus spp. are isolated from infections of domestic animals and can present resistance to different antimicrobials. This study aimed to identify the main species of Enterococcus and determine the phenotypic resistance to antimicrobials of isolates of this bacterial genus obtained from dogs and cats admitted to a veterinary hospital in southern Brazil. A total of 57 Enterococcus spp. were isolated from different clinical samples (urine, feces, ears and skin) in domestic animals admitted to the hospital over a period of three years (2016 to 2019). MALDI-TOF results demonstrated the occurrence of Enterococcus faecium (39; 68.4%), Enterococcus faecalis (17; 29.8%) and Enterococcus avium (1; 1.8%). In an overall analysis, resistance was observed to the antimicrobials rifampicin (46; 80.7%), tetracycline and streptomycin (42; 73.7%), ampicillin and imipenem (41; 71.9%), erythromycin (39; 68.4%), gentamicin (38; 66.7%), ciprofloxacin (36; 63.2%), norfloxacin (32; 56.1%), nitrofurantoin (10; 17.5%) and chloramphenicol (9; 15.7%). None of the Enterococcus spp. showed resistance to vancomycin and linezolid. Multidrug resistance (MDR) was detected in 45 (78.9%) isolates. In conclusion, E. faecium and E. faecalis with MDR are frequent in infections of hospitalized dogs and cats from southern Brazil.